(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the level of personality authenticity among kindergarten teachers, the level of cognitive beliefs among kindergarten teachers, and the correlation between personality authenticity and cognitive beliefs among kindergarten teachers. To achieve the research objectives, the two researchers built a measure of personality authenticity, which consists of (32) distributed items. On (4) areas: (self-awareness, unbiased processing, true self, relationship with others), as well as constructing a measure of cognitive beliefs consisting of (32) items distributed over (4) areas: (learning control, simple knowledge, learning speed, Stability of knowledge), and after verifying the cytometric properties and discriminatory power of the two scales, the two scales were applied to the research sample of (350) kindergarten teachers, The two researchers used the Statistical Package for the Social Sciences (SPSS) to analyze the data statistically, and the results showed: 1- Kindergarten teachers have original personality. 2- Kindergarten teachers have cognitive beliefs. 3-There is a positive correlation between the originality of personality and the cognitive beliefs of kindergarten teachers.